Republic of Estonia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on the Republic of Estonia underlies gross and net international investment positions. Capital gains have been exceptionally beneficial to Malta's external position, but have significantly worsened Estonia's NIIP, and to a lesser degree, positions in Hungary and Slovenia. In examining the economic and institutional composition of gross international investment positions, the differences between those in Cyprus and Malta, and in the other new member states is stark. Greater financial integration is associated with greater economic openness, but the influence of levels of economic development is mixed.